Silencing “Top-Down” Cortical Signals Affects Spike-Responses of Neurons in Cat’s “Intermediate” Visual Cortex - Huang, Jin Y.; Wang, Chun; Dreher, Bogdan (Frontiers in Neural Circuits, 2017)
We examined the effects of reversible inactivation of a higher-order, pattern/form-processing, postero-temporal visual (PTV) cortex on the background activities and spike-responses of single neurons in the ipsilateral cytoarchitectonic area 19 (putative area V3) of anaesthetized domestic cats. Very occasionally (2/28), silencing recurrent ‘feedback’ signals from PTV, resulted in significant and reversible reduction in background activity of area 19 neurons. By contrast, in large proportions of area 19 neurons, PTV inactivation resulted in: i) significant reversible changes in the peak magnitude of their responses to visual stimuli (35.5%; 10/28); ii) substantial reversible changes in direction selectivity indices (43%; 12/28) and iii) reversible, upward shifts in preferred stimulus velocities (37%; 7/19). Substantial (≥ 20°) shifts in preferred orientation and/or substantial (≥ 20°) changes in width of orientation tuning curves of area 19 neurons were however less common (26.5%; 4/15). In a series of experiments conducted earlier, inactivation of PTV also induced upward shifts in the preferred velocities of the ipsilateral cytoarchitectonic area 17 (V1) neurons responding optimally at low velocities. These upward shifts in preferred velocities of areas 19 and 17 neurons were often accompanied by substantial increases in direction selectivity indices. Thus, in both the primary visual cortex and the ‘intermediate’ visual cortex (area 19), feedback from PTV plays a modulatory role in relation to stimulus velocity preferences and/or direction selectivity, that is, the properties which are usually believed to be determined by the inputs from the dorsal thalamus and/or feedforward inputs from the primary visual cortices. The apparent specialization of area 19 for processing information about stationary/slowly moving visual stimuli is at least partially determined, by the feedback from the higher-order pattern-processing visual area. Overall, the recurrent signals from the higher-order, pattern/form-processing visual cortex appear to play an important role in determining the magnitude of spike-responses and some ‘motion-related’ receptive field properties of a substantial proportion of neurons in the intermediate form-processing visual area - area 19.